Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian dan Program Pascasarjana Universitas Sriwijaya - MULYANA, ANDY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008, 2012)
The objective of the research is to find out the position of fresh fruit bunch (FFB) price of oil palm determined by regional government in a range of its price predicted by bilateral monopoly market approach, meaning that whether it have protected plasma farmers and reaching a price that reflected balance bargaining positions, or it tended to come close to a monopsonist price or to monopolist price. Three nucleus estate smallholders (NES) types was selected as samples to be examined their condition and data (1998-2002) in this research, which were NES-Transmigration managed by private and public firms, and NES of small scale credit type. Single equations analyses of econometric model were used to estimate FFB price and volume in constructing demand and supply curves of the commodity. The results show that the determined FFB price is proven to have protected farmers from monopsonist price application without that intervention. However, the its level in bilateral monopoly market perspective, in which KUD representing farmers as a monopolist, still closed to monopsonist price. This also reflects stronger bargaining power of the nucleus firm than the plasma farmers, and the status of FFB price as a derivation of world CPO price. More strong commitment and serious attempt are needed from both sides to increase partnerships works in order to obtain fair FFB price in the future.
Keywords: Oil Palm, Fresh Fruit Bunch (FFB), CPO, NES, Price, Monopsony, Monopoly, Bilateral Monopoly